Faktor–Faktor Yang Memengaruhi Purchase Intention Sayur Organik Pada Konsumen Mahasiswa Di Yogyakarta - Khaerunisa, Almira Cindy; Tinaprilla, Netti; Purwono, Joko; Cindy Khaerunisa, Almira (Forum Agribisnis, 2025)
Concerns about the negative impact of agricultural production that uses chemicals intensively on environmental sustainability and human health have resulted an increase organic consumption, especially organic vegetables. Important to know the factors that influence purchase intentions toward organic vegetables. Intentions can be studied using the Theory of Planned Behavior (TPB) model including attitudes towards behavior, subjective norms, and perceived behavioral control. Previous research also found that environmental concern, health concern, and product availability have an influence to that product. The purpose of this research is to analyze the Factors Influencing Purchase Intention Toward Organic Vegetable, especially by student as potential customer, it can help producers to formulate managerial implications. This research was conducted in Yogyakarta with a total 230 respondents. This research uses descriptive analysis, Partial Least Square (PLS-SEM), and Importance Performance Matrix Analysis (IPMA). The results of this study show that purchase intention organic vegetables is influenced by attitudes towards behavior and perceived behavioral control, while subjective norms do not influence purchase intention. Attitudes towards behavior in this study were influenced by environmental concern and health concern, perceived behavioral control were influenced by product availability. The managerial implication that can be carried to increase attitude toward behavior which is known to have the highest importance value through increasing environmental concern and health concern which influences students attitudes towards behaviour to purchasing intentions of organic vegetables in Yogyakarta.